1992
DOI: 10.1111/j.1467-9450.1992.tb00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric differences in the perception of words and faces in deaf and hearing children

Abstract: The purpose of this study was to investigate hemispheric functional asymmetry in 18 normal hearing children and 18 congenitally deaf children aged 13-14 years. The task was identification of a visual stimulus (3-letter word or photograph of a face) presented in either the left or right visual field. The children responded by pointing to the target stimulus on a response card which contained four different words or three different faces. The percentage of errors for presentations to the two visual fields were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
2
3
0
1
Order By: Relevance
“…A similar pattern was observed across the primary and secondary emotion tasks, in which participants detected either happy or angry faces, respectively. These results extend the findings of previous studies of face perception in the deaf, which report reduced or reversed visual field asymmetries during perception of emotional faces (Vargha-Khadem, 1983; Szelag and Wasilewski, 1992; Szelag et al, 1992; Corina et al, 1999). These studies were often limited by the use of different stimuli across tasks, by the inclusion of linguistic information in the stimuli (e.g., linguistic facial expressions or manual signs), or by task demands that involved linguistic processing (Corina, 1989; Vargha-Khadem, 1983).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A similar pattern was observed across the primary and secondary emotion tasks, in which participants detected either happy or angry faces, respectively. These results extend the findings of previous studies of face perception in the deaf, which report reduced or reversed visual field asymmetries during perception of emotional faces (Vargha-Khadem, 1983; Szelag and Wasilewski, 1992; Szelag et al, 1992; Corina et al, 1999). These studies were often limited by the use of different stimuli across tasks, by the inclusion of linguistic information in the stimuli (e.g., linguistic facial expressions or manual signs), or by task demands that involved linguistic processing (Corina, 1989; Vargha-Khadem, 1983).…”
Section: Discussionsupporting
confidence: 90%
“…This hypothesis is in line with previous evidence that visual field and hemispheric asymmetries in the deaf are altered during the perception of both emotional and linguistic expressions (Vargha-Khadem, 1983; Szelag and Wasilewski, 1992; Szelag et al, 1992; Corina et al, 1999; McCullough et al, 2005) and that these effects may be influenced by task demands (Corina, 1989). The current results are also consistent with evidence from our own lab that hemispheric asymmetries of face-sensitive event-related potentials in deaf signers are not altered during perception of neutral faces or during same/different face discriminations (Mitchell et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some findings are compatible with this prediction. A preliminary study on error rate during a recognition task with lateralized visual presentation suggested a left-hemifield superiority for faces and a right hemifield superiority for words in hearing children, whereas deaf children presented similar scores for both visual fields and even a left-hemifield superiority for words (Szelag et al 1992). In the same direction, an fMRI study reported an atypical leftward lateralization of the FFA during the recognition of facial expression in deaf subjects (McCullough et al 2005) whereas activation was bilateral for hearing subjects.…”
Section: Impact Of Language Lateralization On Vwfa and Ffamentioning
confidence: 98%
“…Öte yandan doğuştan sağır olan 13-14 yaşındaki çocukların yüz işleme görevinde (Szelag, Wasilewski & Fersten 1992) ve yüzdeki duyguyu değerlendirmede sağır olmayan çocuklardan farklı olarak herhangi bir hemisferik asimetri göstermedikleri gözlenmiştir. Söz konusu bulgular işitsel bilginin işlenmediği bir beyinde, yüz işlemeye ilişkin olarak da bir özelleşmenin ortaya çıkmadığına işaret etmektedir.…”
Section: Sağlıklı Ve Hasta Grupların Karşılaştırılmasıunclassified